Non-symbiotic soil microbes are more strongly influenced by altered tree biodiversity than arbuscular mycorrhizal fungi during initial forest establishment. Issue 10 (22nd August 2019) - Grossman, Jake J; Butterfield, Allen J; Cavender-Bares, Jeannine; Hobbie, Sarah E; Reich, Peter B; Gutknecht, Jessica; Kennedy, Peter G
ABSTRACT: While the relationship between plant and microbial diversity has been well studied in grasslands, less is known about similar relationships in forests, especially for obligately symbiotic arbuscular mycorrhizal (AM) fungi. To assess the effect of varying tree diversity on microbial alpha- and beta-diversity, we sampled soil from plots in a high-density tree diversity experiment in Minnesota, USA, 3 years after establishment. About 3 of 12 tree species are AM hosts; the other 9 primarily associate with ectomycorrhizal fungi. We used phospho- and neutral lipid fatty acid analysis to characterize the biomass and functional identity of the whole soil bacterial and fungal community and high throughput sequencing to identify the species-level richness and composition of the AM fungal community. We found that plots of differing tree composition had different bacterial and fungal communities; plots with conifers, and especially Juniperus virginiana, had lower densities of several bacterial groups. In contrast, plots with a higher density or diversity of AM hosts showed no sign of greater AM fungal abundance or diversity. Our results indicate that early responses to plant diversity vary considerably across microbial groups, with AM fungal communities potentially requiring longer timescales to respond to changes in host tree diversity. Abstract : We found that, 3 years after planting a tree diversity experiment, soil microbial community diversity (but not AM fungal diversity) tracked the experimentally varied composition of tree communities.